STRATEGIC PLANNING FOR DEVELOPMENT OF LOCAL COMMUNITIES-MODEL MZ GLOGONJ - Cvijanović, Drago; Hamović, Vladana; Subić, Jonel (Economics of Agriculture, 2011)
Editors: Prof. Dr Drago Cvijanović, Dr Vladana Hamović, doc. Dr Jonel Subić Publisher: Institute of Agricultural Economics, Belgrade, 2010.